An overview of rural-urban migration in South Africa: its causes and implications - Mlambo, Victor (Archives of Business Research, 2018)
The failure of the government to prioritise rural development threatens to negatively impact the development of growth of rural areas. Rural-urban migration in South Africa has negatively affected socio-economic development in rural areas. By strictly analysing relevant literature related to rural-urban migration in South Africa, it became evident that rural provinces have been witnessing a huge outflow of people destined for urban areas, predominately to Gauteng and the Western Cape province, this has robbed rural areas of skills and innovation, which has prolonged the cycle of underdevelopment. The influx of people to urban areas has also strained government resources, increased population-growth and increased housing infrastructure challenges. The government has been slow react in addressing the problem and as a result, numerous skilled professionals have left rural areas, crippling service delivery. Frequent cooperation with local leaders and more investment in rural areas are needs to fight rural-urban migration.